2014
DOI: 10.1002/hpm.2258
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the shortage of village doctors in China and solutions under the policy of basic public health service equalization: evidence from Changzhou

Abstract: As the most important public health service providers in rural China, village doctors are facing a new challenge of heavier workload resulting from the recent policy of public health service equalization. Studies on the shortage of village doctors, mainly based on the national statistics, have so far been very broad. This study conducted detailed field surveys to identify specific factors of and potential solutions to the shortage in village doctors. Eight hundred forty-four village doctors and 995 health deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…The study in Changzhou County indicated that village doctors felt difficult to provide all the required items of public health services. Most village doctors (92.3%) complained about the "low salary" and "lack of social security" [20]. Our former study in five counties of China also [21] evinced that only 41.3% of the village doctors had pension, and the proportions varied from 2.3% to 83.3% among different counties because the pension were supported by local finance.…”
Section: Introductionmentioning
confidence: 67%
“…The study in Changzhou County indicated that village doctors felt difficult to provide all the required items of public health services. Most village doctors (92.3%) complained about the "low salary" and "lack of social security" [20]. Our former study in five counties of China also [21] evinced that only 41.3% of the village doctors had pension, and the proportions varied from 2.3% to 83.3% among different counties because the pension were supported by local finance.…”
Section: Introductionmentioning
confidence: 67%
“…As previous studies have suggested, a sufficient pension plan is critical for retention of village doctors in rural areas [34–38]. However, through various pilot programs [39, 40], NRPP has still not achieved the goal, mainly due to the low return rate [15]. As such, NRPP is limited to being a supplementary income for village doctors after retirement, rather than sufficient support [41].…”
Section: Discussionmentioning
confidence: 99%
“…According to one statistical report, the percentage of rural doctors aged over 60 years rose from 3.1% in 2002 to 13.6% in 2010. 4 The number of rural doctors decreased from 1.13 per 1000 rural residents in 2002 to 0.81 per 1000 rural residents in 2010 despite a population increase in these areas during the same period. The government must take urgent action to encourage more medical school graduates and other young health workers to work in rural areas, to expand medical insurance coverage, and to invest in better medical equipment and facilities in rural areas.…”
Section: [Image: Guang Lu]mentioning
confidence: 98%